2018
DOI: 10.1021/jacs.8b09809
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Role of tBP–LiTFSI Complexes in Perovskite Solar Cells

Abstract: Lead halide-based perovskite materials have been applied as an intrinsic layer for next-generation photovoltaic devices. However, the stability and performance reproducibility of perovskite solar cells (PSCs) needs to be further improved to match that of silicon photovoltaic devices before they can be commercialized. One of the major bottlenecks that hinders the improvement of device stability/reproducibility is the additives in the hole-transport layer, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
173
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(177 citation statements)
references
References 53 publications
4
173
0
Order By: Relevance
“…We would like to note that the lithium salt, Bis(trifluoromethylsulfonyl)amine lithium salt (LiTFSI), is widely employed as a beneficial additive in the PSCs in both the ETL and HTL . Specifically in TiO 2 , LiTFSI has been shown to downshift the conduction band, resulting in higher photocurrents and improved electron transport within the mesoporous TiO 2 by partial reduction of Ti 4+ to Ti 3+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We would like to note that the lithium salt, Bis(trifluoromethylsulfonyl)amine lithium salt (LiTFSI), is widely employed as a beneficial additive in the PSCs in both the ETL and HTL . Specifically in TiO 2 , LiTFSI has been shown to downshift the conduction band, resulting in higher photocurrents and improved electron transport within the mesoporous TiO 2 by partial reduction of Ti 4+ to Ti 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, the benefits of Li have been most commonly associated with increased conductivity and charge densities, both of which are more favorable in the p ‐type dopant LiTFSI . While it is known that LiTFSI is a vital additive in the HTL for PSCs, its benefit to the TiO 2 layer have only been observed using LiTFSI. This suggests that the TFSI − anion is playing a crucial role in performance enhancement and can likely be associated with its conductivity .…”
Section: Resultsmentioning
confidence: 99%
“…Literatures have shown that oxygen and moisture trigger phase segregation and decomposition of absorber layer . Meanwhile, the Spiro‐OMeTAD is degraded faster with the assistance of moisture . In addition, the thermal stability tracked at 85 °C is shown in Figure S12 (Supporting Information), and the UVCA with paraffin encapsulated device also present much better stability than that without paraffin‐encapsulated devices.…”
Section: Resultsmentioning
confidence: 99%
“…Pristine 2,2′,7,7′‐Tetrakis( N,N ‐ di‐p ‐methoxyphenylamine)‐9,9′‐spirobifluorene (spiro‐OMeTAD), the most commonly used HTM in PSCs, suffers from low hole mobility and thus exhibits a relatively poor efficiency . To achieve high‐efficiency PSCs, chemical dopants such as Li‐TFSI and Co(III) salts are necessary for spiro‐OMeTAD to increase the conductivity . Actually, Li‐TFSI is a chemical mediator that can promote the reaction between spiro‐OMeTAD and O 2 in atmosphere .…”
Section: Methodsmentioning
confidence: 99%